Os desafios e as contribuições do Programa Nacional de Alimentação Escolar (PNAE) para o fortalecimento da agricultura familiar camponesa em Itapicuru/BA - Matos, Murilo Mateus Soares de (2020)
This research aims to analyze the challenges and the PNAE contributions for peasant family farming in the municipality of Itapicuru/BA. The National School Feeding Program (PNAE), regulated by Law 11.947/2009, establishes in its guidelines that at least 30% of the financial resources transferred by the National Education Development Fund (FNDE), be used to purchase products from peasant family farming, preferably from agrarian reform settlements, indigenous and quilombo communities. We found that this guideline was implemented as of 2017 in the municipality with the inclusion of food produced by local farmers in school meals. This achievement was the result of the farmers’ movement and the intervention of CAE members on the municipality managers, in view of the problems related to the production and circulation of food produced by local farmers. The methodological procedures are based on case study, the research has a qualitative basis, it is structured by a theoretical review about the theme, survey of quantitative data, field research and systematization of the information collected. The results show the obstacles faced by farmers to enter the program, the change in the program management led to the insertion of food produced by a reduced number of peasant family farmers in the institutional market for school meals and the income generated is considered complementary, contributes to social reproduction and to stay in the countryside.